Links between rural electrification and gendered off-farm employment in sub-Saharan Africa - Jessy Amarachi Ezebuihe; Martin Christoph Parlasca; Matin Qaim (University of Bonn, Center for Development Research (ZEF), 2024)
We analyze the relationship between household electricity access and off-farm employment of women and men in rural Africa, using primary survey data from Kenya, Namibia, Tanzania, and Zambia. Estimating regression models, we find that access to electricity is positively associated with women's off-farm employment status, labor hours, and earnings. For men, access to electricity is significantly associated only with off-farm earnings. Further, we differentiate between the sources of electricity accessible to households and find gendered differences between grid electricity and off-grid solar home systems. While solar home systems are not significantly associated with any of the employment outcomes for men, they are positively and significantly associated with women's off-farm employment status and earnings. We explore differences in gendered time use between electrified and non-electrified households, and also analyze the main purposes of electricity use and perceived impacts on people's lives to help explain the regression estimates. Our results suggest that electricity access and its sources have different implications for women's and men's daily routines and off-farm employment. The findings have relevance for policy, given that access to off-farm income is important not only for the wellbeing and resilience of rural households, but also for gender equity and female financial autonomy.
Keywords: C21; C24; J21; J22; Q12; Q41; 330; gender; grid electricity; off-grid solar; rural Africa; rural jobs